Tracking Religious Moderation Discourse Content on Student’s Final Paper in Indonesian Islamic Higher Education - Abdul Gaffar; Abdul Muiz Amir; Akbar Akbar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
Abstract Albeit research into religious moderation at Indonesian Islamic Higher Education (PTKIN) has been widely undertaken, little empirical research reports on tracing students’ final works as critical research to examine the alignment of PTKIN’s vision in support of government programs to build an inclusive and moderate discourse on religious understanding distribution. This study employs Tracing of Research Studies in three steps, taxonomy analysis, citation analysis, and statistical analysis of diversity. The analysis was conducted on Qur’an and Hadith theses and dissertations published by five institutions. The findings indicate that the religious moderation discourse established in PTKIN’s dissertation and thesis truly conveys the ambiguity of its concept. The ideas employed in the research obscured the government's concepts in establishing religious moderation in the Indonesian setting. This research proposes that mainstreaming religious moderation in PTKIN be implemented more thoroughly, particularly in compiling students’ final papers. Abstrak Meski telah banyak penelitian terkait moderasi beragama di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN), penelitian empiris yang menelusuri karya akhir mahasiswa masih terbatas, khususnya kajian kritis untuk mengeksplorasi keselarasan perwujudan visi dan misi PTKIN dalam mendukung program pemerintah untuk menciptakan paham keagamaan yang bersifat inklusif dan moderat. Penelitian ini menerapkan Tracing of Research Studies dengan tiga langkah analisis yaitu analisis taksonomi, analisis kutipan, dan analisis statistik keragaman. Analisis tersebut dilakukan terhadap tesis dan disertasi Al-Qur’an dan Hadis yang diterbitkan oleh 5 PTKIN. Hasil penelitian menunjukkan bahwa diskursus yang dikembangkan dalam tesis dan disertasi PTKIN justru mengesankan ambiguitas gagasan moderasi beragama. Gagasan yang digunakan dalam penelitian mengaburkan konsep yang telah dikonsep oleh pemerintah sebagai pedoman untuk mencapai moderasi beragama dalam konteks keIndonesiaan. Penelitian ini menyarankan agar strategi pengarusutamaan moderasi beragama di PTKIN dilakukan secara lebih komprehensif khususnya dalam produksi karya tulis akhir mahasiswa.